Influence of tactical variables on attacking actions in elite soccer - Moreno del Castillo, R.; Nardi, A.; Zubillaga, A.; Fradua, L. (Kinesiologia Slovenica, 2017)
The aim of this study was to analyze the influence of tactical variables on attacking actions in elite soccer match-play. A total of 1417 attacking actions were collected from ten Spanish LaLiga and English Premier League matches from 2006-2007 season. The Amisco® match analysis system was employed to collect data. The following variables were included for the analysis: pass number, players number, duration, starting zone (SZ) and final zone (FZ). The results showed that 24.3% of these actions where performed without passes, the remaining 57%, 11,6% and 7,1% were performed with = 3, 4-6, and = 7 consecutive passes. Furthermore, one third (25,9%) of these offensive actions involved a single player, while the remaining 74,1% (collective actions) involved 2-5 players and = 6 players for a 65,6% and 8,5%, respectively. Finally, according to the five classes of duration the 49,3%, 26,4%, 12%, 13% and 6,5% of these offensive actions were lasting 24 seconds, respectively. The analysis of the 9 zones, grouped in 3 areas of intervention, showed as 39.1% of actions started into the defensive area, 42.0% into the midfield area and only 18.9% into the attacking area. The variables analyzed should be considered when analyzing attacking actions in elite soccer.